Energy saving in wastewater treatment plants: A plant-generic cooperative decision support system. (20th November 2017) - Torregrossa, Dario; Hernández-Sancho, F.; Hansen, J.; Cornelissen, A.; Popov, T.; Schutz, G.
Abstract: In Europe, the analysis of Waste Water Treatment Plants (WWTPs) shows a significant energy efficiency potential (up to 25%). Optimistically, plant managers assess their plant efficiency once or twice per year. Consequently, the time gap between an inefficiency and its detection produces avoidable operational costs. Although the installation of multiple on-line sensors can provide detailed energy information, for a human operator it is unrealistic to analyse the produced data in a satisfactory time-scale. This paper proposes a cooperative tool for energy saving that remotely accesses and evaluates WWTP databases to produce daily energy assessment reports. The novelty of this decision support tool lies in the original combination of: key performance indicators, daily benchmarking, expert knowledge, scenario analysis, fuzzy logic and shared knowledge. In this paper, the Shared Knowledge Decision Support System (SK-DSS) concept is presented and the methodology demonstrated and validated on the energy consumption of biological aeration systems. Highlights: In Europe, the analysis of WWTPs shows a high energy effciency potential. Currently, WWTPs databases find very limited use and data is often simply stored. Decision Support Systems (DSS) can use this data and support the WWTP management. A plant generic and network-based cooperative DSS is proposed to save energy in WWTPs. This DSS has been successfully tested on the multi perspective analysis of aeration.